The Influence of Lynn White, jr.'s Medieval Technology and Social Change - Worthen, Shana (History compass, 2009)
Lynn White, jr. published Medieval Technology and Social Change in 1962. A reflection of his lifelong interest in the Middle Ages, combined with his realization of the benefits of studying a civilization through its material culture, White's work helped to create the field of the history of medieval technology. Controversial, inspiring, and accessible, the influence of this book continues to affect the work of a wide variety of scholars. White's contentious ‘stirrup thesis’ suggested that the stirrup's introduction to Europe from Asia in the Carolingian period enabled the development of feudalism, which concept was itself highly problematic. His work on the plow, the horse harness, and three-field crop rotation, and the degree to which they affected Europe's post-Roman population shift, is still debated. Mechanical power may not have led to a medieval industrial revolution as White claimed, but wind, water, and chemical power developments, along with the development of the crank, still substantially altered medieval agricultural and industrial production. Medieval Technology and Social Change, for all its flaws, is still a highly readable work of history, in part because of its multi-disciplinary use of archeology, etymology, economic history, art history, and iconography to frame its central sociocultural and technological arguments, and it is used widely by historians of the Middle Ages, technology, agriculture, and military history alike. This article surveys the historiography of the book, especially its influence on and discussions in recent histories.